Genetic risk factors for cerebral small-vessel disease in hypertensive patients from a genetically isolated population. Issue 1 (28th July 2010) - Schuur, M; van Swieten, J C; Schol-Gelok, S; Ikram, M A; Vernooij, M W; Liu, F; Isaacs, A; de Boer, R; de Koning, I; Niessen, W J; Vrooman, H; Oostra, B A; et al.
Abstract : Background: Asymptomatic cerebral lesions on MRI such as white matter lesions (WML), lacunes and microbleeds are commonly seen in older people. We examined the role of a series of candidate genes involved in blood pressure regulation and amyloid metabolism. Materials and Methods: The study was embedded in a family-based cohort sampled from a Dutch genetically isolated population. We selected individuals between 55 and 75 years of age with hypertension (N=129). Volumes of WML and presence of lacunes and microbleeds were assessed with MRI. We studied three genes involved in blood pressure regulation (angiotensin, angiotensin II type 1 receptor, α-adducin) and two genes involved in the amyloid pathway (apolipoprotein E ( APOE ) and sortilin-related receptor gene ( SORL1 )). Results: All participants had WML (median volume, 3.1 ml; interquartile range, 1.5–6.5 ml); lacunar infarcts were present in 15.5% and microbleeds in 23.3%. Homozygosity for the APOE ε4 allele was associated with lacunes (OR, 4.8; 95% CI, 1.2 to 19.3). Individuals carrying two copies of the variant allele of four single nucleotide polymorphism (SNPs) located at the 3′-end of SORL1 (rs1699102, rs3824968, rs2282649, rs1010159) had significantly more often microbleeds (highest OR, 6.87; 95% CI, 1.78 to 26.44). Conclusion: The association of SORL1 with microbleeds suggests that the amyloid cascade is involved in the aetiology of microbleeds in populations with hypertension.